THE RELATIONSHIP BETWEEN KNOWLEDGE AND DISASTER PREPAREDNESS IN NURSING STUDENTS STIKES YATSI TANGERANG IN 2021 - Octaviana, Fanisha; Jaenudin, Jaenudin (Journal of Vocational Nursing, 2022)
Introduction: The occurrence of disasters in 2017-2021 reached 12,199 disasters consisting of floods, tornadoes, landslides, forest fires, earthquakes, abrasion, and volcanic eruptions. Many disasters have resulted in 4,851 deaths and 39,633 people missing and injured (BNPB, 2021). Methods: This research is a quantitative correlation study with a cross-sectional approach. The sampling technique used in this study was total sampling, which consisted of 335 respondents from nursing students at STIKes Yatsi, Tangerang. Data collection was done by distributing questionnaires. Data analysis using chi-square test. Results: The results showed that most female students had a good level of knowledge (55,2%) and preparedness (58,5%). The bivariate analysis results showed a significant relationship between knowledge and disaster preparedness r = 0.016 (r < 0.05). The study concluded that the better the student's knowledge, the better the disaster preparedness. Conclusions: The study found a relationship between knowledge and disaster preparedness in students.